STRATEGI KEPALA SEKOLAH DALAM MENGATASI RESISTENSI GURU TERHADAP INOVASI PEMBELAJARAN DIGITAL - Rasyani, Desinta; Hasmitawati; Eriyani, Elfa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to synthesize findings from the literature on principals’ strategies for addressing teachers’ resistance to digital learning innovations. Using a library research method with a narrative literature review approach, the study extracted evidence from 20 articles comprising qualitative case studies, multiple case studies, literature reviews, and systematic literature reviews. The data were analyzed through thematic coding to map key resistance factors and the leadership strategies most frequently recommended. The synthesis indicates that teachers’ resistance to digital innovation is an ecosystem-level phenomenon closely related to schools’ limited capacity. Dominant barriers include limited budgets and technological infrastructure, gaps in teachers’ and stakeholders’ digital literacy, organizational cultural resistance and conventional mindsets, uneven readiness for implementation accompanied by weak digital mentoring/supervision, and psychological factors such as fear, lack of understanding, and change fatigue. Effective principal strategies are multi-component, encompassing continuous professional development (e.g., training, coaching, mentoring, and learning communities), provision of infrastructure and technical support, visionary or transformational leadership with participatory and empathetic change communication, strengthened stakeholder collaboration, and data-driven monitoring and evaluation (e.g., using LMS data) to support continuous improvement. These findings underscore the need for adaptive, collaborative, and support-oriented digital change leadership to reduce teachers’ resistance and sustain digital learning innovation.